Kleine-Levin Syndrome in an 8-Year-Old Girl with Autistic Disorder: Does Autism Account a Primary or Secondary Cause? - HAKIM SHOUSHTARI, Mitra; GHALEBANDI, Mirfarhad; TAVASOLI, Azita; POURSHAMS, Maryam (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Hakim Shoushtari M, Ghalebandi MF, Tavasoli A, Pourshams M. Kleine-Levin Syndrome in an 8 Year Old Girl with Autistic Disorder Does Autism Account a Primary or Secondary Cause? Iran J Child Neurol. Autumn 2015;9(4):61-64. Abstract Objective Kleine–Levin syndrome (KLS) is a rare disorder with an unknown etiology. Autism spectrum disorder is characterized by various degrees of impairment in social communication, repetitive behavior and restricted interests. Only four patients of KLS with autistic spectrum disorder (ASD) have been reported so far. This report presents an 8-year-old girl with history of autistic disorder and epilepsy that superimposed KLS. Because of the rarity of KLS and related studies did not address whether autism accounts for a primary or secondary cause, the area required attention further studies.